Modeling And Simulation Of Photovoltaic Module With Enhanced Perturb And Observe MPPT Algorithm Using Matlab/Simulink - Al-Shetwi, Ali Q.; Muhamad Zahim, Sujod (Asian Research Publishing Network (ARPN), 2016)
Modeling and analysis of photovoltaic (PV) system is substantial for designers of solar power plants to do a yield investigation that precisely predicts the expected output power under changing weather conditions. The model allows the prediction of PV module’s behaviour and characteristics based on the mathematical model equivalent circuit using Matlab/Simulink platform under different temperature and solar radiation readings. The second part of this paper proposes an enhancement to the conventional perturb and observe (P&O) maximum power point tracking (MPPT) technique in order to overcome the disadvantages of this method such as oscillation and slow tracking under sudden change of atmospheric conditions. The proposed method suggested that utilizing a variable perturbation step size depending on power changes instead of constant step size which is used in conventional P&O algorithm in order to ensure that the solar energy is captured and converted as much as possible. The simulation results are compared with that of traditional P&O to demonstrate the effectiveness of the proposed method.